Enhanced gas sensing properties of indium doped ZnO thin films. (December 2018) - Bharath, S.P.; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: Indium doped ZnO (Inx Zn1-x O, 0 ≤ x ≤ 0.05) thin films were deposited on to soda lime glass substrate by employing spray pyrolysis as deposition technique. Effect of doping concentration on characteristics of thin films were examined by XRD, SEM, UV-Visible spectroscopy, electrical and gas sensing measurements. XRD analysis demonstrates polycrystalline nature of thin films and also shows the shift in orientation from (002) to (101) crystal plane with increase in indium doping concentration. Surface morphological analysis shows the formation of homogeneous particle like nanostructures. Optical transmittance determined from UV-Visible spectroscopy was in the range of 80–95%, which was decreasing with increase in indium doping concentration. Maximum electrical conductivity was achieved at an optimal indium doping concentration of 3 at.%. The gas sensing properties were examined for different concentration of volatile organic compounds like acetone, ethanol and methanol for different doping levels. In0.03 Zn0.97 O thin films showed good sensitivity towards ethanol, with sensitivity of 30% towards 25 ppm of ethanol. Highlights: Indium doped zinc oxide thin films have been synthesized using industrially applicable spray pyrolysis technique. Incorporation of indium into ZnO changes the preferential orientation of grains and modifies surface morphology. Indium doped zinc oxide thin films exhibit the good sensing property for volatile organic compounds. An optimum doping of 3 at.% indium was found to be good for both electrical and gas sensing properties.